CLEAN AND HEALTHY LIVING BEHAVIOR IN THE FAMILY ENVIRONMENT AS A PREVENTION OF COVID-19 IN SERANG CITY - Afrizal, Stevany; Athallaisya Adinda, Inez (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2022)
The rapid spread of the COVID-19 virus throughout the world has come as a complete shock, and it is causing serious concerns. The COVID-19 virus can be prevented with the help of a simple yet highly successful method called "clean and healthy living behavior" (PHBS). The health of family members is expected to improve as a result of the implementation of clean and healthy living behavior (PHBS) in the family environment, which includes adhering to health protocols, staying at home for those who do not have to leave the house, and allowing workers or employees to work from home (Work From Home/WFH). Family participation in PHBS is essential in order to prevent COVID-19 from spreading, as demonstrated by the emergence of COVID-19. The objective of this paper is to educate the community and families about PHBS, as well as to ensure that it is properly implemented. Descriptive qualitative interviews and scientific references are employed to perform the research. The researcher chose this title because he wants to break the chain of the COVID-19 virus's transmission in order to establish a family environment that is mindful of health and enhancing a healthy and clean family environment, so that people do not get sick as easily as before. A healthy family environment can increase productivity, so that family members will get used to implementing PHBS and children can grow up healthy and have adequate nutrition.